Conditining factors of the decision-making in processes of entrepreneurial organizations: the case of the banana plantain context in Nicaragua - Lázaro Angulo SJ, A.E. (2008)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica), 2008